(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article focuses on pilgrim theology, which includes many different fields. The five main fields are exegesis (drawing out the meaning of the biblical texts), biblical theology (tracing the history of redemption and the promises of God from Genesis to Revelation), systematic theology (discerning what the Bible as a whole says about a particular topic), church history (examining God’s providence in Christ’s body), and practical (or applied) theology (exploring the application of theology in everyday life). Some people would see apologetics (defending the faith against various forms of unbelief) as part of systematic theology, whereas others would see it as a separate field of its own. Each of these main fields has various branches.